(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to assess the financial performance of Al-Qasim Green University through the use of some financial evaluation indicators, which included liquidity and profitability indicators, and presentation of data for the period 8 201-2019, as well as identifying the role of other financial indicators in the evaluation. The research reached a group of Recommendations, the most important of which is the need for the university to rely on the financial performance evaluation process in order to reach all of its strengths and weaknesses in order to improve its future performance